The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fmats.2020.00020
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of pH on the Preparation of Electrically Conductive and Physically Stable PANI/Sago Blend Film via in situ Polymerization

Abstract: This study attempts to prepare electrically conductive and physically stable PANI/Sago starch films by a simple one-pot synthesis method using ultrasound irradiation technique. To attain physical stability of the prepared films, the pH of the PANI/Sago dispersion was varied (2, 4, 6, 7, 9, and 11 pH) before drying. The effect of pH on the structural properties (1 H NMR and FT-IR), electrical conductivity (E.C), optical properties (UV-VIS), and morphology (FE-SEM) of the blends was studied. 1 H NMR results reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…The most commonly used synthesis methods for PPy are chemical and electrochemical polymerization 37,38 . Recently, the ultrasonic‐irradiation‐assisted polymerization of PPy has also gained research interest 39‐41 . Other synthesis methods for PPy include vapor‐phase polymerization (VPP), electrospinning, microemulsion polymerization, mechanochemical polymerization, and photopolymerization.…”
Section: Synthesis Of Ppymentioning
confidence: 99%
“…The most commonly used synthesis methods for PPy are chemical and electrochemical polymerization 37,38 . Recently, the ultrasonic‐irradiation‐assisted polymerization of PPy has also gained research interest 39‐41 . Other synthesis methods for PPy include vapor‐phase polymerization (VPP), electrospinning, microemulsion polymerization, mechanochemical polymerization, and photopolymerization.…”
Section: Synthesis Of Ppymentioning
confidence: 99%
“…The findings indicate similar patterns to those in the study of dose variation and time variation. As stated in the literature, with the change in conductivity, the absorbance at 600 nm also changes inversely.…”
Section: Resultsmentioning
confidence: 54%
“…The relationship between charge and doping has been well explained by MacDiarmid and Huang as the protonation/deprotonation of PANI, which results in an increase or decrease in the amount of charge on the polymer backbone, leading to increased or decreased conductivity. 69 , 70 The relationship between charge and doping has been explained in a study reported in the literature, 71 which mentioned that during the deprotonation of PANI, the interaction between a polar molecule and PANI decreases, which results in redistribution of charge and hence reduced electrical conductivity. Thus, based on the above discussions, it can be inferred that on the addition of NaOH to the protonated PHPM dispersion, the deprotonation of PANI starts.…”
Section: Resultsmentioning
confidence: 99%
“…An abrupt change occurs between pH 8 and pH 9 owing to the dedoping point ( Figure 6 ). At pH 6 and pH 7, it is observed that the intensity of bipolaron decreases until pH 8, whereas, at pH 9 and pH 10, the polaron broadband shows a blue shift, presenting a new band around ~600 nm characteristic of an emeraldine base structure [ 51 ]. In our previous work, the dedoping point of the PAni doping with AMPS manifested itself at pH 4.4 [ 37 ].…”
Section: Resultsmentioning
confidence: 99%